Sleep Quality in Patients with Human Immunodeficiency Virus - Aqilah, Faiha Nurul; Pramukti, Iqbal; Nugraha, Bambang Aditya; Lukman, Mamat; Harun, Hasniatisari; Sithichoksakulchai, Siriluk (Poltekkes Kemenkes Tanjung Karang, 2024)
Human Immunodeficiency Virus (HIV) is a viral infection that occurs in the human immune system and makes the body unable to fight infection because the virus can replicate itself. The physical and psychological problems experienced by HIV patients can change their sleep patterns and quality. Poor sleep quality will cause various health problems, including a decreased immune system. HIV patients have experienced a decrease in their immune system due to viral infection, so they need good quality sleep so as not to disrupt their condition and health status. This research was conducted to determine the quality of sleep of HIV patients at Sumedang Hospital. This research method is descriptive and quantitative, with 74 HIV patients taken using consecutive sampling techniques. The sleep quality assessment instrument uses the Pittsburgh Sleep Quality Index (PSQI). Univariate analysis was used in this study to describe the distribution of frequencies and percentages of respondent characteristics and sleep quality. The results of this study showed that the majority of HIV patients experienced poor sleep quality (63.5%). Poor sleep quality that occurs in HIV patients is related to various factors such as psychological stress, disease, medication, age, and gender. From these findings, efforts, and interventions are needed for nurses or health service providers to improve the sleep quality of HIV patients.